The Role of Information Technology Professionals in Maintaining Integrity and Moral Responsibility in Modern Digital Work Environments - Ni Putu diah Pradnya Savitri; Ni Putu Miskha Putri Karendya; Ni Putu Maylia Mustikasari; Ni Putu Mitha Pebriana Mulya; Paskalis Fanjaya Datul; Ocalia Yasinta Dimut (Journal of Digital Law and Policy, 2026)
This study aims to examine the role of Information Technology (IT) professionals in maintaining integrity and moral responsibility within modern digital work environments characterized by rapid technological advancement and increasing ethical complexity. The research employs a qualitative approach by combining a systematic literature review and conceptual analysis of scholarly publications, professional codes of ethics, and relevant regulatory documents at both international and Indonesian levels. The findings reveal that IT professionals play a strategic role in ensuring data privacy protection, cybersecurity risk management, prevention of algorithmic bias, and the development of ethical software and digital governance practices. Furthermore, the study highlights the importance of continuous ethics training, strong organizational policies, interdisciplinary collaboration, and transparent reporting mechanisms in supporting ethical decision-making among IT practitioners. Integrating global ethical standards with local cultural values, particularly the principles of Pancasila, is found to strengthen moral responsibility and professional integrity in the Indonesian digital context. This study implies that ethical governance in IT not only enhances organizational trust and regulatory compliance but also contributes to the sustainability and accountability of digital work environments. The findings offer practical insights for organizations, policymakers, and educators in strengthening ethical frameworks and promoting responsible digital practices.